(untitled) (Research, Society and Development, 2024)
Objectives: Obtain information in the scientific literature regarding dysbiosis and celiac disease, in order to elucidate whether such alteration is a cause or consequence of the pathology in question, as well as measures to control and treat the disease. Methodology: This review was conducted in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) guidelines. Inclusion criteria included works that analyze the relationship between intestinal microbiota and celiac disease, published from 2015 to 2023 in the bibliographic databases PUBMed, Scielo and Biblioteca Virtual em Saúde. Results: After removing abstracts based on the inclusion and exclusion criteria, 16 articles were obtained eligible for inclusion in this review. Conclusions: The intestinal microbiota is an important factor in maintaining the immune status and understanding celiac disease. In patients with the disease, changes in the composition of the intestinal microbiota are observed. There is a need for studies aimed at observing the relationship between the topics covered.